Physiological and molecular characterization of two coffea arabica cultivars under diferent heat stress conditions - Ferrara-Barbosa, Bárbara Castanheira (2016)
Coffee is one of the most valuable primary products in world trade. Its cultivation, processing, transport, and marketing employs over 120 million people and significantly affects the gross national product (GNP) of 40 countries. Worldwide, coffee is grown on over 10,000,000 hectares of land. Smallholder farmers cultivate over 70% of production, making coffee crucial to the economy of many developing countries. Currently, Brazil is the world's leading producer of coffee, a position the country has held for the last 150 years, p o n o hly 40% of h wo l ’ pply of A b b n across more than 2,000 farms in 16 states. According to the Intergovernmental Panel on Climate Change (2014), there is a high probability of temperature increases of 1 to 3°C in the tropics over the next 20 years. The losses to Arabica coffee production, as a result of increasing temperatures, are estimated to be as much as 10% of total production in 20 years. Therefore, in the face of imminent climate changes, the development of cultivars that are tolerant to adverse environmental conditions is essential. To that end, the identification of the key genes involved in plant responses to abiotic stress is critical for improving the crop by either traditional breeding or genetic transformation. Hence, we aimed to understand the impact of heat stress at the physiological and molecular levels on the growth and development of coffee. Moreover, we aimed to identify the genes that are differentially transcribed in response to high temperatures, which may lead to the future development of cultivars with improved quality and higher harvest security.